Gallic acid and its alkyl esters emerge as effective antioxidants against lipid oxidation during hot air drying process of Ostrea talienwhanensis. (March 2021) - Zhao, Man-Tong; Liu, Zhong-Yuan; Li, Ao; Zhao, Guan-Hua; Xie, Hong-Kai; Zhou, Da-Yong; Wang, Tong
Abstract: The antioxidant efficiency of gallic acid (GA) and its alkyl esters including methyl gallate (MG), ethyl gallate (EG), propyl gallate (PG), butyl gallate (BG), octyl gallate (OG), lauryl gallate (LG), hexadecyl gallate (HG), and octadecyl gallate (SG) in oyster tissue during hot-air drying process was investigated. Results indicated that GA and its alkyl esters all could effectively retard lipid oxidation in oyster tissue according to peroxide value (POV), thiobarbituric acid reactive substances (TBARS) and free radical intensity. The antioxidant effects increased with the alkyl chain length until OG, thereafter, it gradually decreased. The POV of the OG treated oysters post 10 h of drying was 66.26, 68.90, 77.86, 92.61, 89.45, 70.79, 68.96 and 62.70%, respectively, of those treated by GA, MG, EG, PG, BG, LG, HG and SG. The corresponding values for TBARS were 68.72, 76.59, 77.88, 84.32, 86.23, 68.31, 81.24, 77.36%, while 41.19, 58.62, 62.83, 64.49, 69.60, 61.44, 60.05 and 72.61% for free radical intensity. Pearson correlation analysis showed a positive correlation between the antioxidant effects and the concentrations of the polyphenol compounds in oyster tissue. This report will provide the basic data for selection of suitable antioxidants to improve the oxidation stability of seafood during thermal processing. Highlights: Gallic acid alkyl esters retarded oyster lipid oxidation during hot-air drying. Some gallic acid alkyl esters showed better antioxidant effects than gallic acid. Antioxidant efficiency of gallic acid alkyl esters showed "cut-off effect". Efficiency of gallic acid alkyl esters positively correlated with penetrated content.